ASSESSMENT OF THE SPECIAL PHYSICAL AND THE SPECIFIC TECHNICAL PREPAREDNESS OF BASKETBALL PLAYERS - Milena Aleksieva (Izdevnieciba "Baltija Publishing", 2016)
The purpose of this study is to optimize the training process of the best basketball players (16-years-old) from the national team - cadets of Bulgaria, through analysis and evaluation of their special physical fitness and specific technical-tactical preparedness. Subject of the study is the basketball game in between growing up competitors-boys. Object of the study is the main signs of the special physical fitness and specific technical-tactical preparedness in the basketball in the age of 16. Contingent of the study is 18 basketball players, listed in the composition of the Bulgarian national team for the respective age group under study. For achieving the objective and tasks of the study, data for 14 indicators are registered (for physical preparedness - 9 indicators and for technical-tactical preparedness - 5 indicators).